Influência da laparoscopia e da laparotomia na gasometria, leucometria diferencial e citocinas em modelo de sepse abdominal em ratos - Araújo Filho, Irami (2005)
Laparoscopic surgery is associated with reduced surgical trauma, and less acute phase response, as compared with open surgery. Cytokines are important regulators of the biological response to surgical and anesthetic stress. The aim of this study was to determine if CO2 pneumoperitoneum would change cytokine expression, gas parameters and leukocyte count in septic rats. Methods: Wistar rats were randomly assigned to five groups: control (anesthesia only), laparotomy, CO2 pneumoperitoneum, cecum ligation and puncture by laparotomy, and laparoscopic cecum ligation and puncture. After 30 min of the procedures, arterial blood samples were obtained to determine leukocytes subpopulations by hemocytometer. TNFα, IL-1β, IL-6 were determined in intraperitoneal fluid (by ELISA). Gas parameters were measured on arterial blood, intraperitoneal and subperitoneal exsudates. Results: Peritoneal TNFα, IL-1β and IL-6 concentrations were lower in pneumoperitoneum rats than in all other groups (p<0.05). TNFα, IL-1β and IL-6 expression was lower in the laparoscopic than in laparotomic sepsis (p<0.05). Rats from laparoscopic cecum ligation and puncture group developed significant hypercarbic acidosis in blood and subperitoneal fluid when compared to open procedure group. Total white blood cells and lymphocytes were significantly lower in laparoscopic cecum ligation and puncture rats than in the laparotomic (p<0.01). Nevertheless, the laparotomic cecum ligation rats had a significant increase in blood neutrophils and eosinophils when compared with controls (p<0.05). Conclusions: This study demonstrates that the CO2 pneumoperitoneum reduced the inflammatory and immune response in an animal model of peritonitis with respect to intraperitoneal cytokines, white blood cell count and clinical correlates of sepsis. The pneumoperitoneum produced hypercarbic acidosis in septic animals